Good fiction guide - Rogers, Jane.; Lee, Hermione; Harris, Mike.; Houston, Douglas (Oxford : Oxford University Press, 2001)
A reference book on English language fiction to inspire and enlighten all readers. An alphabetically arranged list of authors gives concise information on writers classical and contemporary, literary and popular, British and foreign, and recommends other writers hwo deal with similar subject matter or who write in the same genre. The book also includes 34 essays by well recognized authors and critics discussing diverse literary genres
Keywords: Fiction; English fiction; American fiction; Authors